A novel hybrid fixation (coracoclavicular screw supplemented with K-wire) for the treatment of acute acromioclavicular joint dislocation: A prospective study. (November 2018) - Zheng, Junju; Chen, Jiaru; Chen, Lin; Ni, Yueping; Lin, Zhou
Abstract: Objective: The aim of this study was to compare the radiological and clinical outcomes of clavicular hook plate fixation and the coracoclavicular lag screw supplemented with K-wire fixation in the treatment of acute acromioclavicular joint dislocation. Methods: Between January 2012 to December 2015, 81 patients with acute acromioclavicular joint dislocation were included in this prospective study. 43 patients were treated with clavicular hook plate fixation (Group A) and 38 patients were treated with coracoclavicular lag screw supplemented with K-wire fixation (Group B). Incision length, operation duration, blood loss volume, intraoperative fluoroscopy times and length of hospitalization were recorded. Radiographic outcomes, functional outcomes and complications were also recorded. Results: Both two groups could achieve good radiographic and functional outcomes after operation. Group B exhibited significantly shorter operation duration, shorter length of incision, less blood loss volume and shorter length of hospitalization than Group A (P < 0.001). In addition, significant difference could be found between the two groups regarding the VAS scores three month postoperatively and the final follow-up (P < 0.001). However, there was no significant difference in radiographic and functional outcomes between the two groups (P > 0.05). Conclusion: The two groups can both achieve satisfactory radiological and functional outcomes in treating acute AC joint dislocation. However, CC screw fixation supplemented with K-wire exerts some advantages regarding the incision length, operation duration, blood loss volume, length of hospitalization. Furthermore, it can better relieve the pain caused by dislocation. Therefore, the novel hybrid fixation (CC screw fixation supplemented with K-wire) provides an alternative treatment for acute AC joint dislocation. Highlights: Both two groups could achieve satisfactory outcomes in treating acute acromioclavicular joint dislocation. CC screw fixation supplemented with K-wire has advantages over clavicular hook plate fixation in term of some respects. CC screw fixation supplemented with K-wire provides an alternative treatment for acute AC joint dislocation.